2021
DOI: 10.1186/s12913-020-05942-8
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study to identify critical attributes and attribute-levels for a discrete choice experiment on oral pre-exposure prophylaxis (PrEP) delivery among young people in Cape Town and Johannesburg, South Africa

Abstract: Background The uptake and adherence of daily oral PrEP has been poor in high-risk populations in South Africa including young people. We used qualitative research methods to explore user preferences for daily and on-demand oral PrEP use among young South Africans, and to inform the identification of critical attributes and attribute-levels for quantitative analysis of user preferences, i.e. a discrete choice experiment (DCE). Methods Data were coll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
1
13
1
Order By: Relevance
“…A methodological contribution of the study lies in both a detailed description of the attribute identification process, including the number of steps and tools: (1) a literature review, (2) focus groups with targeted populations using Think Aloud technique interview guides, and (3) a ranking exercise. The rationale behind using the Think Aloud technique in DCE studies was discussed previously in the literature, but studies that describe the experience with this technique are limited [ 35 37 ]. The lessons learned from using the technique are described below.…”
Section: Discussionmentioning
confidence: 99%
“…A methodological contribution of the study lies in both a detailed description of the attribute identification process, including the number of steps and tools: (1) a literature review, (2) focus groups with targeted populations using Think Aloud technique interview guides, and (3) a ranking exercise. The rationale behind using the Think Aloud technique in DCE studies was discussed previously in the literature, but studies that describe the experience with this technique are limited [ 35 37 ]. The lessons learned from using the technique are described below.…”
Section: Discussionmentioning
confidence: 99%
“…The PrEP delivery setting preferences of these people, mainly HIV testing and outpatient services, could inform on the preferences of people who do not regularly frequent health services. Another limitation is that we did not consider other potential places for PrEP refill and follow-up such as pharmacy or specific community health center [ 14 ]. A population-based survey among 2498 men and women in west Kenya showed that both men and women prefer getting PrEP in clinics (44%) followed by pharmacies (38%) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…MSM, sex workers), but remains scarce in general population. Existing studies suggest that groups from the general population prefer receiving PrEP from general health services rather than from a specialized clinic [ 12 14 ]. In the United States, a survey of 370 Black women accessing medical care for sexual health or urgent care needs showed they preferred PrEP delivery through “a regular source of healthcare” as opposed to sexually transmitted infection (STI) or family planning clinics [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DCEs are a well-established quantitative method that elicits stated preferences based on responses to described hypothetical scenarios. The response data are used to calculate the utility of each attribute level and the relative importance associated with each attribute [40][41][42][43][44]. Tradeoff estimates can also be calculated using the utility values.…”
Section: Methodsmentioning
confidence: 99%